Seleção de estirpes de rizóbios e efeitos da inoculação Rhizobium japonicum - Glomus macrocarpum, baixa dosagem de fósforo e calagem no desenvolvimento da soja tropical (Glycine max (L.) Merrill). - Nunes, Luís Alfredo Pinheiro Leal (1994)
The purpose of this work was to select efficient strains of Rhizobium japonicum adaptaded to the semi-arid tropic and to evaluate the effects of the jointly inoculation of Rhizobium japonicum— Glomus macrocarpum, low dosage of phosphorus and liming on the development of the tropical soybean (Glycine max (L.) Merril). The research was conducted on Campus of the Federal University of Ceará, and the selection of strains was developed under laboratory conditions, in a growth chamber and inoculated in culture tubes with Norris solution agarized, free of nitrogen. The tubes were fertilized every 10 days with Norris solution (10m1/tubes). A completely randomized experimental design was used with 15 treatments and 03 replicates. The strains 392-A, 381-A 123-B and 701-A were more efficient, improving significately shoot dry weight and nodulation of the roots. Two experments were also settled in the greenhouse. In both experiments a completely randomized experimental design was used, each with 09 treatments and 05 replicates. The parcels consisted of black bags of polyethylen with 3kg of a Yellow Latosol, from Regeneração county, Piaui State, Brazil, containing 5ug/cm3 of phosphorus and pH 4.3 (Experiment II). In the Experiment I the pH of soil was corrected to 6.4 using dolomitic calcareous in the equivalent dosage of 10g/parcel, 30 days before seeding. A mixture of the best strains that were outstanding in the selection test was inoculated on seeds and the mycorrhizal fungus Glomus macrocarpum was applicated, in the form of spores, on filter paper placed 5cm below seeds inoculated with Rhizobium japonicum. Triple superphosphate (0,36g/parcel) was usedd as a source of phosphorus. Everyweek the nutritive solution of Hewitt, free of nitrogen and phosphorus, was applied in each plastic bag, except in the non-inoculated control. The plants of both experiments were harvested after 45 days. At that time height, dry weight, nitrogen and phosphorus contents of the shoots, percentage of mycorhizal colonization, nodulation of the roots and the spore number of soil were determined. Low dosage of phosphorus applied increased the number of spores of arbuscular mycorrhizal fungi, the absorption of phosphorus by plants, the rhizobial nodulation inoculated plants and, consequently, increasing nitrogen fixation and the development of soybean, in both experiments. Liming increased efficiency of the inoculation with Rhizobium japonicum and Glomus macrocarpum and the development of the plants in acid soil. Jointly inoculation of Rhizobium japonicum and Glomus macrocarpum was better than inoculation of each symbiont individually.